Age-related changes of serum mitochondrial uncoupling 1, rumen and rectal temperature in goats. (July 2016) - Arfuso, Francesca; Rizzo, Maria; Giannetto, Claudia; Giudice, Elisabetta; Fazio, Francesco; Piccione, Giuseppe
Abstract: Thermoregulatory processes are induced not only by exposure to cold or heat but also by a variety of physiological situations including age, fasting and food intake that result in changes in body temperature. The aim of the present study was to evaluate the differences in serum mitochondrial uncoupling protein 1 (UCP1), rumen temperature (TRUMEN ) and rectal temperature (TRECTAL ) values between adult and kids goats. Ten adult male Maltese goats aged 3–5 years old (Group A) and 30 male kids, raised for meat, were enrolled in this study. The kids were equally divided into 3 groups according to their age: Group B included kids aged 3 months, Group C included kids aged 4 months and Group D included kids aged 5 months. Blood samples and measurements of TRUMEN and TRECTAL were obtained from each animal. One-way repeated measures analysis of variance (ANOVA) was applied to evaluate the effect of age on the studied parameters. Statistically significant higher serum UCP1 levels (P<0.001) were found in Group A as compared to Groups B, C and D. Higher TRUMEN values (P<0.001) were found in Group A than in Groups B, C and D, and in Group B than in Groups C and D. Group A showed lower TRECTAL values (P<0.001) than Groups B, C and D. The Pearson's Correlation test was applied to assess significant relationship among studied parameters showing a statistically significant negative correlation between the values of TRECTAL and serum UCP1 in all studied Groups (P<0.001). These results indicate that goats have good control of body temperature suggesting that further details about the thermogenic capacity and the function of UCP1 in kids and adult goats are worth exploring. Highlights: Age effect on serum UCP1, rumen and rectal temperature values was studied in goats. Significant changes occurred on all studied parameters. UCP1 resulted negatively correlated with rectal temperature in adult goats. UCP1 resulted negatively correlated with rectal temperature in young goats. Lower UCP1 values may serve to offset body heat loss in young goats.